Objectives, design and main findings until 2020 from the Rotterdam Study - Ikram, M. Arfan; Brusselle, Guy; Ghanbari, Mohsen; Goedegebure, André; Ikram, M. Kamran; Kavousi, Maryam; Kieboom, Brenda C. T.; Klaver, Caroline C. W.; de Knegt, Robert J.; Luik, Annemarie I.; Nijsten, Tamar E. C.; Peeters, Robin P.; et al. (European journal of epidemiology, 2020)
The Rotterdam Study is an ongoing prospective cohort study that started in 1990 in the city of Rotterdam, The Netherlands. The study aims to unravel etiology, preclinical course, natural history and potential targets for intervention for chronic diseases in mid-life and late-life. The study focuses on cardiovascular, endocrine, hepatic, neurological, ophthalmic, psychiatric, dermatological, otolaryngological, locomotor, and respiratory diseases. As of 2008, 14,926 subjects aged 45 years or over comprise the Rotterdam Study cohort. Since 2016, the cohort is being expanded by persons aged 40 years and over. The findings of the Rotterdam Study have been presented in over 1700 research articles and reports. This article provides an update on the rationale and design of the study. It also presents a summary of the major findings from the preceding 3 years and outlines developments for the coming period.